Some Mechanisms of Testicular Toxicity of Polychlorinated Biphenyls - E. F. Agletdinov (Антибиотики и Химиотерапия)
The effects of polychlorinated biphenyls on the reproductive system were studied on adult male rats. The results of the experiments showed that the polychlorinated biphenyls significantly decreased the number of the spermatogenesis cells and spermatozoa in the testicular tissue. In addition, increased peroxidation and failure of non-enzymatic and enzymatic antioxidants were observed. The results suggested that the revealed disorders could play an important role in pathogenesis of male infertility, caused by environmental pollutants.